Zero Food Waste: Pemanfaatan Maggot Sebagai Solusi Pengelolaan Limbah Organik Di SD Laboratorium UPI Purwakarta - Alfiana Nurussama; Dona Reza Sudirja; Kania Pratiwi; Khaerani Nurfaoziah; Najayanti; Paola Pebriyanti; Sarah Nabilah (CV. Multi Kreasi Media, 2024)
Maggot, the larvae of the Black Soldier Fly (Hermetia illucens), offer an effective solution in organic waste management. Maggots have an amazing ability to decompose organic waste in a short period of time, converting it into nutrient-rich biomass. This process starts from hatching eggs into larvae, which consume waste until it reaches the pupa stage. The use of maggot provides various benefits, including reducing the volume of organic waste, producing high-quality organic fertilizers, and providing cheap and nutritious animal feed. Therefore, this research is focused on supporting preservation in the UPI Purwakarta Labschool Elementary School. With the efficiency and benefits offered, maggot is a sustainable solution in overcoming the problem of organic waste while having a positive impact on the economy and ecosystem in school.